Pembuatan mikrokristalin selulosa dari ubi jalar (Ipomoea batatas (L.) Lamk.) dengan Avicel PH 102 sebagai pembanding dan evaluasi mutu fisik - Shinta Mida Ariani Harahap; Gabena Indrayani Dalimunthe; Minda Sari Lubis; Rafita Yuniarti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Microcrystalline cellulose is an excipient used in the manufacture of directly felt tablets, namely as a filler, binder, and crushing agent and can be isolated from fibrous plants. One of the abundant fibrous plants in Indonesia is sweet potato (Ipomoea batatas L.). The main chemical composition of sweet potatoes includes carbohydrates, namely dietary fibre (hemicellulose, cellulose), starch, and several types of sugar. The objective of this research was to make microcrystalline cellulose from sweet potato (Ipomoea batatas L.) and see the comparison of physical quality evaluation of microcrystalline cellulose results from sweet potato (Ipomoea batatas L.) with Avicel PH 102. This research used the hydrolysis method of HCl 2.5 N acid by heating at a temperature of 105ºC for 10-15 minutes with the ratio of alpha-cellulose and acid used is (1: 20). Then, evaluated the physical quality of microcrystalline cellulose from sweet potatoes by organoleptic tests, identification, pH determination, solubility of substances in water and drying loss. The results of this research show that sweet potato cellulose can be used as microcrystalline cellulose, namely with the results of a physical quality evaluation that meets the requirements when compared to Avicel PH 102; each includes organoleptic where both are in powder form, do not have the same smell and taste, but there are differences in colour where Avicel PH 102 is white. In contrast, microcrystalline sweet potato cellulose is yellowish-white. On identification, both produce violet blue; pH 5.2 and pH 6.5; solubility of substances in water 0.2% and 0.1%; drying shrinkage of 0.71% and 2.53%; And in the starch test, both did not produce a violet-blue solution.